Antimicrobial utilization data: Does point prevalence data correlate with defined daily doses?. (August 2019) - Lee, Stephen B.; Thirion, Daniel J.G.; Irfan, Neal; Sung, Melani; Brooks, Annie; Al-Mutawa, Fatimah; Frenette, Charles; Mertz, Dominik
Abstract: We correlated antibiotic consumption measured by point prevalence survey with defined daily doses (DDD) across multiple hospitals. Point prevalence survey had a higher correlation (1) with monthly DDDs than annual DDDs, (2) in nonsurgical versus surgical wards, and (3) on high- versus low-utilization wards. Findings may be hospital specific due to hospital differences.